The Dwarf Saltwort (Salicornia bigelovii Torr.): Evaluation of Breeding Populations. (8th July 2012) - Jaradat, Abdullah A.; Shahid, Mohammed
Abstract : Breeding populations of the dwarf saltwort ( Salicornia   bigelovii Torr. (Chenopodiaceae)) have been evaluated under high seawater salinity (45 dS m −1 ) for phenotypic, morphometric, biomass and seed traits to select and develop genotypes for biomass, seed, and vegetable production using sea and brackish water and marginal land resources. The largest variation between populations was found for harvest index and the smallest for number of spikes per plant; however, a more complex structure of variance was found when fixed and random factors were considered. Multivariate relationships between and within architectural and fitness-related traits suggest that biomass and seed yield gains can be achieved by manipulating plant architecture. Discriminant analyses between populations resulted in populations being correctly (mean 83%) classified. Prediction (R 2 ) and validation (Q 2 ) coefficients in the partial least squares regression modeling, using three phenotypic markers, 12 morphometric traits, nine populations and 24 families(populations), were 0.86 and 0.78; respectively (P < 0.002 ) for plant dry weight and 0.89 and 0.83, respectively (P < 0.001 ) for seed yield per plant. We developed a procedure to identify populations and families within populations with favorable combinations of phenotypic and morphometric traits that are suitable for the development of Salicornia varieties for biomass, seed, or green vegetable production.